The Lao Experience in Deploying Influenza A(H1N1)pdm09 Vaccine: Lessons Made Relevant in Preparing for Present Day Pandemic Threats. - Anonh Xeuatvongsa; Sara Mirza; Christian Winter; Keith Feldon; Phengta Vongphrachanh; Darouny Phonekeo; Justin Denny; Viengphone Khanthamaly; Bounheuang Kounnavong; Doualy Lylianou; Sisouphane Phousavath; Sisouveth Norasingh; et al. (PLoS ONE)
The Lao PDR, as did most countries of the Mekong Region, embarked on a pandemic vaccine initiative to counter the threat posed by influenza A(H1N1)pdm09. Overall, estimated vaccine coverage of the Lao population was 14%, with uptake in targeted health care workers and pregnant women 99% and 41%, respectively. Adverse Events Following Immunization accounted for only 6% of survey driven, reported vaccination experiences, with no severe consequences or deaths. Public acceptability of the vaccine campaign was high (98%). Challenges to vaccine deployment included: 1) no previous experience in fielding a seasonal influenza vaccine, 2) safety and efficacy concerns, and 3) late arrival of vaccine 10 months into the pandemic. The Lao success in surmounting these hurdles was in large measure attributed to the oversight assigned the National Immunization Program, and national sensitivities in responding to the avian influenza A(H5N1) crisis in the years leading up to the pandemic. The Lao "lessons learned" from pandemic vaccine deployment are made even more relevant four years on, given the many avian influenza strains circulating in the region, all with pandemic potential.